An Efficient DC-AC Power Integration Model for Single-Phase Systems, Simulated in MATLAB - Pandeya, Supriya; Karki, Menaka (International Journal on Engineering Technology, 2024)
In the face of growing clean energy demands, this study presents a model for integrating Direct Current (DC) sources into the existing Alternating Current (AC) grid. The model is based on a single-phase system where a DC source is added. A converter, designed using the synchronous reference frame, is proposed to address integration issues. This converter allows for the control of both active and reactive power using a dq reference frame. A Proportional-Integrator (PI) controller is chosen for this purpose. To generate the necessary operational references, a Phase-Locked Loop (PLL) is used. An LCL filter is also incorporated based on its performance quality. The entire model is simulated in MATLAB, and the output obtained confirms the model’s ability to control both active and reactive power when integrating DC with AC and T. This work significantly contributes to the efforts of integrating clean energy into our existing grid systems.